2014
DOI: 10.1002/bdra.23305
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the mutational spectrum associated to neural tube defects: Literature revision and description of novel VANGL1 mutations

Abstract: We showed a significant (p = 7.0E-5) association between VANGL1 rare genetic variants, especially missense mutations, and NTDs risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 64 publications
1
19
0
1
Order By: Relevance
“…Interestingly, increased expression of the VANGL2 homologue VANGL1 has been linked to tumor progression and increased malignancy [72, 73]. While both VANGL2 and VANGL1 regulate neural tube closure [74], only VANGL2 is required for PCP during zebrafish gastrulation [75]. Clearly, much remains to be learned about these transmembrane proteins and their functions during embryonic development and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased expression of the VANGL2 homologue VANGL1 has been linked to tumor progression and increased malignancy [72, 73]. While both VANGL2 and VANGL1 regulate neural tube closure [74], only VANGL2 is required for PCP during zebrafish gastrulation [75]. Clearly, much remains to be learned about these transmembrane proteins and their functions during embryonic development and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies of mice have identified more than 240 genes involved in neural tube closure (Harris & Juriloff, 2010;Wilde, Petersen, & Niswander, 2014;Wilson, & Maden, 2005) and this information has provided a framework to explore the genetic causes of NTDs in humans over the past decade (Chen et al, 2017;De Marco et al, 2014;Kibar et al, 2007;Qiao et al, 2016). Genes that function in particular pathways involved in planar cell polarity (PCP), ciliogenesis, the glycine cleavage system and one-carbon metabolism have been explored in a relatively large number of cases (Allache et al, 2015;Cai & Shi, 2014;De Marco et al, 2014;Dowdle et al, 2011;Hopp et al, 2011;Jones, Fiozzo, Waters, McKnight, & Brown, 2014;Kibar et al, 2007;Lei et al, 2013;Lei et al, 2014;Lei et al, 2010;Marini et al, 2011;Merello et al, 2015;Miao et al, 2016;Narisawa et al, 2012;Qiao et al, 2016;Roberson et al, 2015;Robinson et al, 2012;Shaheen et al, 2015;Yang et al, 2013;Zhang et al, 2015). PCP gene variants have been associated with the most severe NTD phenotype, craniorachischisis, as well as more limited NTDs such as myelomeningocele.…”
Section: Introductionmentioning
confidence: 99%
“…Planar cell polarity genes play a critical role in neural tube closure in model organisms. Studies in humans have identified rare nonsynonymous mutations in planar cell polarity pathway genes, including the VANGL genes, that may play a role as risk factors for NTDs (Merello et al, ). Mutational analysis of three (patients 1, 2, 3) of four patients was performed.…”
Section: Discussionmentioning
confidence: 99%